Hasil Persilangan dan Heterosis Padi Varietas Nasional IPB3S x Varietas Lokal Beak Ganggas - Aryana, I Gusti Putu Muliarta; Wangiyana, I Wayan; Sukartono, Sukartono; Nurhasanah, Nurhasanah (LPPM Universitas Mataram, 2025)
The objective of this study was to determine the success rate of hybridization and the heterosis level in rice resulting from the cross between the national variety IPB3S and the local variety Beak Ganggas. To achieve this goal, the following research activities were conducted: A) Single and reciprocal cross hybridization between IPB3S × Beak Ganggas and Beak Ganggas × IPB3S. B) Evaluation of the F1 generation and its parents using a Randomized Complete Block Design (RCBD) with four treatments and six replications, followed by the calculation of heterosis and heterobeltiosis values. The hybridization was carried out in the greenhouse of the Faculty of Agriculture, University of Mataram, while the evaluation of the hybridization results was conducted in the rice fields of Nyurlembang Village, Narmada District, West Lombok Regency. The research was conducted from February to September 2025. The results showed that the percentage of filled grains from the single cross IPB3S × Beak Ganggas was 68.61%, while the percentage from the reciprocal cross (Beak Ganggas × IPB3S) was 37.28%. Based on heterosis and heterobeltiosis values, the F1 hybrid of IPB3S/Beak Ganggas has strong potential to be developed as a promising ideal-type variety, due to its superior combination of traits such as earlier flowering time, shorter plant height, and higher number of filled grains and grain weight per clump compared to its parent lines.